Nonwoven from cigarette butt applied in pre-treatment of surface water - Vielmo, Ana Silvia de Lima; Rodrigues, Ailton Borges; Rosa, Eduardo Volkart da; Domingos, Dayane Gonzaga; Schallemberger, Juliana Barden; Nagel-Hassemer, Maria Eliza (Anuário do Instituto de Geociências, 2022)
This study aimed to evaluate a nonwoven (NW) production and performance from cellulose acetate fiber from cigarette butts andapplied to a filtration system for surface water pre-treatment. The system had a surface area of 528 cm2, cellulose acetate from cigarette butt as filter media, was used and was fed with surface water from a pond. In order to evaluate the treatment performance of the filtration system were evaluated in the raw water (RW) and the filtered water (FW) the classical parameter of water quality as turbidity, total suspended solids (TSS), apparent color, true color, and total organic carbon (TOC) and heavy metals (iron, copper, and cadmium). Moreover, the presence of nicotine was investigated in the FW. The results showed a mean removal efficiency in order to 62.01%, 54.42%, 50.36 %, 6.73%, and 5.20% for turbidity, TSS, apparent color, true color, and TOC, respectively. The removal of metals varied in the order of 72.26%, 9.61%, and 2.12% for cadmium, iron, and copper, respectively. The presence of nicotine in RW and FW was not identified. In this way, besides reducing the negative environmental impacts caused by cigarette butts present in the environment, the developed technology showed potential for removing pollutants present in surface waters.